Strategies to prevent postoperative delirium: a comprehensive evaluation of anesthesia selection and drug intervention - Lan, Shaoze; Liang, Shuai; Wu, Huiwen; Deng, Shihao; Sun, Kenan; Ye, Canming; Yang, Liu; Ciren, Lunzhu; Li, Jun (Frontiers in Psychiatry, 2024)
Postoperative delirium (POD) represents a common neurological complication encountered predominantly among the elderly cohort undergoing surgical intervention for hip fractures. This phenomenon, particularly commonplace in geriatric populations with heightened preoperative risk profiles, pronounced comorbidities, and later stages of lifespan, poses complex clinical challenges. The impact of perioperative pharmacological interventions and anesthetic strategies on POD’s emergence cannot be understated, as it may profoundly affect the length of hospital stays, rehabilitation milestones, and the overall mortality hazard. The pharmacotherapeutic landscape for managing POD remains constrained, underscoring the imperative nature of preventive measures. Prudent preoperative risk stratification, meticulous intraoperative neuromonitoring guided by electroencephalographic studies, and a holistic postoperative patient welfare model are cornerstone recommendations in the quest to mitigate POD’s incidence. Nonetheless, an extensive exploration into the influence of anesthetic approaches and perioperative medications on the emergence of POD is yet to be satisfactorily charted. Our investigation endeavors to dissect the nexus between anesthetic modalities, perioperative pharmacological interventions, and POD incident rates among the elderly with hip fractures. This study spotlights pivotal determinants of POD in the wake of hip fracture surgery by evaluating and synthesizing data from peer-reviewed sources that adhere to rigorous inclusion criteria. Preliminary studies have revealed that certain anesthesia protocols and perioperative medications may increase the potential incidence of POD, such as higher depth of anesthesia or benzodiazepine use, and the incidence of POD in specific populations, such as patients with higher age, prior history of psychosis, and lower intraoperative oxygen saturation The findings from this study are instrumental in refining strategic perioperative plans tailored for the elderly recipients of hip fracture surgery, aimed at not only diminishing the incidence but also the gravity of POD. Despite these forward steps, the clinical uncertainty concerning the efficacy and safety of the specific drugs and surgical techniques in question remains. These lingering questions underscore the exigency for more extensive, empirically grounded research to consolidate the learnings of this investigation.